English literature and the invention of atheism, 1564–1611 - Buchanan, F (2020)
By the 1580s, Western European writers were discussing atheism with increasing urgency. The Greek term ἄθεος and its Latin equivalent atheos had largely fallen out of use since the decline of the Roman Empire. When these terms were readopted in the early sixteenth century, first by writers in France and soon after in Germany, Italy, and the British Isles, they immediately gained currency, becoming central to political, religious, and literary discourses. This thesis examines writing about atheists and atheism in sixteenth-century England from the 1560s to the early seventeenth century. Rather than seeking historical evidence for rising levels of ‘real’ atheism during this period, this thesis explores the role of literature in ‘inventing’ atheism as a cultural category. I use ‘unbelief’ to refer to lack of belief in the existence of God or gods and argue that ‘atheism’ is a conceptualisation of unbelief explicitly developed to attack and discredit unbelievers. Following an initial survey of the histories of atheism and unbelief, I examine the objectives and rhetorical strategies of three forms of writing in which the development of early modern conceptions of atheism is most visible. Firstly, dialogues with fictive atheists written by John Lyly, George Gifford, and Philip Sidney; secondly, the religious polemics of William Whitaker, William Rainolds, and Henry Smith; and finally, dramatic representations of atheism by Christopher Marlowe. These chapters demonstrate that atheism is a hostile designation of unbelief which emerged in response to post-Reformation anxieties about religious division and the recovery of ancient philosophies of unbelief, such as Epicurean annihilationism and Stoic pantheism. Ultimately, this thesis shows how literary techniques that allow motives and inner convictions to be inferred as ‘character’ and ‘voice’ contributed to the emergence of the atheist as a powerfully imagined cultural presence in dialogues, plays, and polemics.